Virtual machine instantiation performance assessment using virtualization infrastructure management - Quintela, João Afonso Amaral (2020)
Two of the most talked technologies nowadays in the networking industry are Software Defined Networks (SDN) and Network Function Virtualization (NFV), whose functioning is supported by virtualization infrastructure management technologies. In this dissertation, one of the technologies that was studied was Openstack, responsible for the creation and management of public and private clouds. In this context, this dissertation presents an extended analysis of the impact of the characteristics and configurations for different types of virtual machines, in the associated instantiation times. The results show that, for the different tested images, the instantiation times differ with the size and complexity of those images.